Hubungan Tingkat Stres dengan Tekanan Darah Menjelang Ujian OSCE pada Mahasiswa Fakultas Kedokteran UKRIDA - Ainullah Nurrahmah; Anna Maria Dewajanti; Winarsi Rudiharso (Jurnal MedScientiae, 2023)
The Objective Structured Clinacal Examination (OSCE) is one of the clinical competency assessment method that has been tested and widely used especially in the field of medical education. The aim of this research is to find out the relationship between stress levels and blood pressure ahead of the OSCE exam for students of UKRIDA medical faculty. This research used cross sectional Study. Sampling in this study using total sampling technique is the whole of the population to be researched using questionnaires. To determine the relationship variables, this research used the statistical test Chi Square. The total sample obtained was 66 samples. The results of this study indicate that students aged 22 years experience more stress than older people and stress is more common in women than men. The level of stress experienced by students before the OSCE is a normal stress level. The blood pressure experienced by students is optimal blood pressure. Based on statistical tests, it shows that there is a relationship between stress levels and blood pressure before OSCE in UKRIDA FK students with p value = 0.004